Experimental and numerical investigation on bearing capacity of granular soil affected by particle roundness - Ghalehjough, Babak Karimi; Akbulut, Suat; celik, Semet (NATL INST SCIENCE COMMUNICATION-NISCAIR, 2017)
Main objective of this study is investigation effect of roundness of particles on ultimate bearing capacity (UBC) of soil. A strip footing was modeled and UBC has been gained at three roundness groups of angular, rounded and well-rounded soil. Two other factors of size and relative density were added to tests for better understanding of soil behavior at different conditions. Tests have been done at 3 roundness groups, 6 size groups from 0.30mm to 4.75mm and 3 relative densities of 30%, 50% and 70%. On next step direct shear tests done at all 54 different conditions. Values from shear box test were compared with experimental results. Comparison showed acceptable relations between theory and experimental results. UBC decreased by increasing roundness of particles. Changing angular soil to well-rounded shape decreased the UBC about 33% at relative density of 30%. This decrease was about 40% at Dr=50%. Ultimate bearing capacity of well-rounded sample was 45% less than angular samples at Dr=70%. It means effect of roundness on UBC was more considerable at bigger relative densities. Same behavior was seen at bigger sizes. Finally changing shape of particles from angular to rounded soil had more effect on decreasing UBC than changing rounded to well-rounded soil.
Keywords: Granular Soil; Ultimate Bearing Capacity; Particle Roundness; Strip Footing; REINFORCED SOIL; STRIP FOOTINGS; SHAPE; SAND; FOUNDATION; Oceanography